Cadmium Toxicity and its Effects on Growth and Metal Nutrient Ion Accumulation in Solanaceae Plants - Halil Samet; Sevda Dursun; Yakup Çıkılı (Journal of Agricultural Sciences)
The effect of cadmium Cd toxicity was studied in four Solanaceae plants tomato, Solanum lycopersicum L.; pepper, Capsicum annuum L.; eggplant, Solanum melongena L., and goldenberry, Physalis peruviana L. grown in greenhouse under natural light conditions. The soil was treated with five levels of Cd 0, 2.5, 5, 10 and 20 mg kg-1 . Except for the tomato, the shoot and root dry biomass decreased with increasing Cd. Plant growth, bioaccumulation and translocation of Cd and accumulation of metal nutrient ions [potassium K , calcium Ca , magnesium Mg , sodium Na , iron Fe , manganese Mn , copper Cu and zinc Zn ] were investigated. On the basis of the percent reductions in the shoot dry biomass, the tomato was determined to be Cd-tolerant, and the other plants Cd-sensitive. The shoot and root Cd contents, uptakes, and total accumulation rate TAR were increased with increasing rate of Cd applied, except for the shoot Cd content and root uptake of the goldenberry. The bioconcentration factor BCF and the translocation factor TF of Cd diminished at all plants, with the exception of the TF for tomato. With respect to Cd translocation, plant species showed a ranking as follows: goldenberry